Clientelism, corruption and the rule of law. (October 2022) - Lindberg, Staffan I.; Lo Bue, Maria C.; Sen, Kunal
Highlights: We study the relationship between political clientelism, corruption and the rule of law. We use a unique panel of developing and developed countries tracked from 1900 to 2018. We distinguish between 'one-shot' clientelism (vote buying) and relational clientelism (non programmatic party linkages). Country-time differences in governance quality are significantly explained by differences in political clientelism. Vote buying and clientelistic party linkages are positively related to corruption. Most of the deleterious effects of political clientelism on the rule of law is conveyed through clientelistic party linkages. Abstract: It is widely believed that clientelism-the giving of material goods in return for electoral support-is associated with poorer governance outcomes. However, systematic cross-country evidence on the deleterious effects of clientelism on governance outcmes is lacking. In this paper we examine the relationship between political clientelism, corruption and rule of law using cross-country panel data for 134 countries for the period 1900–2018. We distinguish between two manifestations of political clientelism-whether vote buying exists, and whether political parties offer material goods to their constituents in exchange for political support (non-programmatic party linkages). We provide evidence of a negative relationship existing between political clientelism on governance outcomes, with increases in clientelism leading to increased political corruption, and weaker rule of law. We also find that the deleterious effects of political clientelism are mainly through non-programmatic party linkages rather than the practice of vote buying.